Method for strengthening leaching of valuable metals in waste lithium battery positive electrode material

By crushing the positive electrode sheet of the used lithium battery and mixing it with organic acid, silica and metal salt in a water bath ultrasonic pot, the problem of low recycling efficiency of valuable metals in the used lithium battery is solved, and efficient metal ion leaching and Recycle.

CN119391990APending Publication Date: 2025-02-07JIANGSU UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411574438.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

How to efficiently recycle valuable metals rich in waste lithium batteries, such as cobalt, nickel, manganese and lithium, to avoid heavy metal pollution.

Method used

By crushing the positive electrode sheet of the used lithium battery into active powder and mixing it with organic acid, silica and metal salt in a water bath ultrasonic pot, the cavitation bubbles caused by ultrasonic waves and catalyst silica are used to promote the dissolution of metal ions.

Benefits of technology

The leaching efficiency of valuable metals in the positive electrode materials of waste lithium battery is improved, and the leaching rate of cobalt and lithium is significantly increased, achieving effective metal recycling and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391990A_ABST
    Figure CN119391990A_ABST
Patent Text Reader

Abstract

The invention discloses a method for strengthening leaching of valuable metals in a waste lithium battery positive electrode material, and relates to the field of waste battery material recovery, and the method comprises the following steps: S1, obtaining a positive electrode plate of a waste lithium battery, and crushing to obtain positive electrode active powder; s2, the three-necked flask is placed in a water bath ultrasonic pot, a left side opening is used for placing a condensation pipe, a central opening is used for placing a stirrer, and a right side opening is used for adding a medicament; s3, adding organic acid into the three-necked flask through a right side opening, and sequentially adding silicon dioxide, metal salt and positive electrode active powder to obtain a mixed solution; s4, uniformly mixing the medicaments in the step S3 by using a water bath ultrasonic pot and a stirrer, and obtaining reacted liquid after the reaction is finished; s5, carrying out solid-liquid separation on the reacted liquid in the step S4, and washing for multiple times to obtain separated solid and liquid; and S6, a set amount of nitric acid is added into the liquid obtained in the step S5, metal hydrolytic precipitation is prevented, then deionized water is used for fixing the volume to 1 L, and leaching liquid containing metal cobalt and lithium is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of waste battery material recycling, in particular to a method for strengthening the leaching of valuable metals in waste lithium battery positive electrode materials. Background Art

[0002] As an ideal environmentally friendly emerging energy source, lithium batteries have the advantages of low cost, good chemical stability, large specific surface area, high conductivity, high specific capacity, excellent rate performance and long cycle life. From 2016 to 2024, the compound annual growth rate of the lithium electronics market is about 10.6%. However, the life of lithium batteries is limited. As a large number of waste lithium batteries enter the "retirement period", more and more waste batteries have begun to become a hidden danger of ecological environment pollution. Therefore, how to deal with and recycle waste lithium batteries has naturally become a problem that people need to face in the end.

[0003] Due to the advantages of lithium batteries such as high energy storage density, long service life and large capacity, they are widely used in the fields of transportation power and power energy storage, and their usage is increasing year by year. It is of great practical significance to transform waste lithium batteries into urban mines. On the one hand, waste lithium batteries are rich in valuable metals such as cobalt, nickel, manganese and lithium. If the metal ions in them can be recycled and reused, it will have good economic benefits; on the other hand, it can also avoid heavy metal pollution caused by improper treatment. Summary of the invention

[0004] The object of the present invention is to provide a method for enhancing the leaching of valuable metals in the positive electrode material of waste lithium batteries, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for enhancing the leaching of valuable metals in the positive electrode material of waste lithium batteries, comprising the following steps:

[0006] S1. Obtain the positive electrode sheet of the waste lithium battery and crush it to obtain the positive electrode active powder;

[0007] S2. Place the three-necked flask in a water bath ultrasonic pot, with the left port for placing the condenser, the central port for placing the stirrer, and the right port for adding the reagent;

[0008] S3. The organic acid was added to the three-necked flask through the right port, and silica, metal salt, and positive electrode active powder were added successively to obtain a mixed solution;

[0009] S4. The reagents in step S3 are mixed evenly using a water bath ultrasonic pot and a stirrer, and the reaction is completed to obtain a liquid after the reaction;

[0010] S5. The liquid after the reaction in step S4 is subjected to solid-liquid separation and washed several times to obtain separated solids and liquids;

[0011] S6. Add a set amount of nitric acid to the liquid described in step S5 to prevent metal hydrolysis and precipitation, and then use deionized water to make the volume to 1L to obtain a leaching solution containing metallic cobalt and lithium.

[0012] Preferably, the waste lithium batteries include a mixture of one or more of lithium cobalt oxide batteries, lithium manganese oxide batteries, lithium iron phosphate batteries, etc.

[0013] Preferably, the organic acid comprises a mixture of one or more of citric acid, malic acid, etc.

[0014] Preferably, the organic acid concentration is 0.15-0.25 mol / L, and the organic acid volume is 40-200 ml.

[0015] Preferably, the mass of the silicon dioxide is 0-160 mg.

[0016] Preferably, the metal salt includes a mixture of one or more of ferrous sulfate, manganese sulfate, cobalt nitrate, nickel sulfate, copper sulfate, etc.

[0017] Preferably, the reaction conditions in step S4 are as follows: the temperature of the water bath ultrasonic pot is 50-90° C., the reaction time is 2-24 h, and the stirrer speed is 400-600 rpm.

[0018] Preferably, the set amount of nitric acid is 0.5-2 ml.

[0019] Preferably, the mass of the metal ions in the metal salt is 40-300 mg.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] In the leaching process of the present invention, cavitation bubbles induced by ultrasound cause continuous contact and separation of solid and liquid, thereby promoting contact electrification to generate active oxygen, and using recyclable silicon dioxide as a catalyst to further improve the leaching efficiency. The use of added metal salts can further enhance the leaching of valuable metals in the positive electrode material of waste lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the X-ray diffraction diagram of the leaching residue of the raw material of the present invention, Example 1 and Comparative Example 1;

[0023] Figure 2 is a scanning SEM image of the leached residue of Example 1 of the present invention;

[0024] Figure 3 is a scanning SEM image of the leached residue of Example 27 of the present invention;

[0025] Figure 4The effects of different metal salts on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries were investigated in Examples 1-4 of the present invention and Comparative Example 1;

[0026] Figure 5 The present invention's Example 1 and Examples 5-7 investigate the effects of different volumes of citric acid on the leaching rates of cobalt and lithium in waste lithium cobalt oxide batteries;

[0027] Figure 6 The effects of different qualities of silicon dioxide on the leaching rates of cobalt and lithium in waste lithium cobalt oxide batteries were investigated in Example 1, Examples 8-10 and Comparative Example 2 of the present invention;

[0028] Figure 7 The present invention's Example 1 and Examples 11-17 investigate the effects of different masses of ferrous sulfate heptahydrate on the leaching rates of cobalt and lithium in waste lithium cobalt oxide batteries;

[0029] Figure 8 The effects of different reaction temperatures on the leaching rates of cobalt and lithium in waste lithium cobalt oxide batteries are investigated in Examples 1 and 18-21 of the present invention;

[0030] Fig. 9 The effects of different reaction times on the leaching rates of cobalt and lithium in waste lithium cobalt oxide batteries are investigated in Examples 1 and 22-26 of the present invention;

[0031] Fig.10 It is the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries according to Example 27 of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention provides a method for enhancing the leaching of valuable metals in the positive electrode material of waste lithium batteries, comprising the following steps:

[0034] S1. Obtain the positive electrode sheet of the waste lithium battery and crush it to obtain the positive electrode active powder;

[0035] S2. Place the three-necked flask in a water bath ultrasonic pot, with the left port for placing the condenser, the central port for placing the stirrer, and the right port for adding the reagent;

[0036] S3. The organic acid was added to the three-necked flask through the right port, and silica, metal salt, and positive electrode active powder were added successively to obtain a mixed solution;

[0037] S4. The reagents in step S3 are mixed evenly using a water bath ultrasonic pot and a stirrer, and the reaction is completed to obtain a liquid after the reaction;

[0038] S5. The liquid after the reaction in step S4 is subjected to solid-liquid separation and washed several times to obtain separated solids and liquids;

[0039] S6. Add a set amount of nitric acid to the liquid described in step S5 to prevent metal hydrolysis and precipitation, and then use deionized water to make the volume to 1L to obtain a leaching solution containing metallic cobalt and lithium.

[0040] The waste lithium batteries include a mixture of one or more of lithium cobalt oxide batteries, lithium manganese oxide batteries, lithium iron phosphate batteries, etc.

[0041] The organic acid includes one or more mixtures of citric acid, malic acid, etc., and the organic acid is used as a leaching agent. Since its acidity is weaker than that of inorganic acid, it has a lower environmental burden and is easily degradable, so it shows superiority in metal recovery. Its advantage is not only that some organic acids can act as reducing agents in the leaching process, but also that some specific organic acids have unique spatial structures and electronic effects and can form complexes with metal ions. This complexing can effectively promote the movement of the leaching reaction equilibrium to the direction of metal ion dissolution by reducing the concentration of free metal ions in the solution in chemical kinetics. This dual action mechanism of organic acid in the leaching process makes it an efficient and multifunctional leaching agent.

[0042] The organic acid concentration is 0.15-0.25 mol / L, and the organic acid volume is 40-200 ml.

[0043] The mass of silicon dioxide is 0-160 mg. With the addition of SiO2 catalyst, the leaching rates of lithium ions and cobalt ions show a significant upward trend, among which the lithium ion leaching concentration reaches a maximum value of 56.4%. This result indicates that an appropriate amount of catalyst can significantly enhance the reaction activity in the electrochemical leaching process, and improve the dissolution rate of metal ions by promoting the effective transfer of charge and the progress of chemical reactions.

[0044] The metal salt includes a mixture of one or more of ferrous sulfate, manganese sulfate, cobalt nitrate, nickel sulfate, copper sulfate, etc. The addition of the metal salt can help the leaching of cobalt and lithium ions.

[0045] The reaction conditions in step S4 are as follows: the temperature of the water bath ultrasonic pot is 50-90° C., the reaction time is 2-24 h, and the speed of the stirrer is 400-600 rpm.

[0046] The set amount of nitric acid is 0.5-2 ml.

[0047] The mass of the metal ion in the metal salt is 40-300 mg

[0048] Example 1

[0049] The present invention provides a method for enhancing the leaching of valuable metals in the positive electrode material of waste lithium batteries, comprising the following steps:

[0050] (1) obtaining a positive electrode sheet of a waste lithium cobalt oxide battery and crushing it to obtain a positive electrode active powder;

[0051] Specifically, the waste lithium cobalt oxide battery cells are fully immersed in a certain concentration of NaCl solution to fully discharge them to ensure the safety of the subsequent disassembly process; the battery shell is then sawed open with tools, and the battery is disassembled and classified into positive electrode materials and the remaining parts (negative electrode materials, iron shells, diaphragms and electrolytes); the positive electrode materials are naturally dried, then cut into small square pieces, and baked in a muffle furnace to remove PVDF; the baked positive electrode sheets are crushed by a grinder and sieved to finally obtain positive electrode active powder

[0052] (2) Place the three-necked flask in a water bath ultrasonic pot, with the left port for placing the condenser, the central port for placing the stirrer, and the right port for adding reagents;

[0053] (3) 80 ml of 0.2 mol / L citric acid was added to the three-necked flask through the right port, and 80 mg of silicon dioxide, 0.1986 g of ferrous sulfate heptahydrate, and 400 mg of positive electrode active powder were added in sequence to obtain a mixed solution;

[0054] (4) using a water bath ultrasonic pot and a stirrer at 70° C., ultrasound, and 500 rpm for 4 h to mix the reagents described in step (3) evenly, and after the reaction is completed, a reacted liquid is obtained;

[0055] (5) subjecting the liquid after the reaction in step (4) to solid-liquid separation, and washing the mixture multiple times to obtain separated solid and liquid;

[0056] (6) Add 1 ml of nitric acid to the liquid in step (5) to prevent metal hydrolysis and precipitation, and then use deionized water to make the volume to 1 L to obtain a leaching solution containing metallic cobalt and lithium.

[0057] Example 2

[0058] The difference from Example 1 is that the metal salt added in step (3) is 0.1974 g of cobalt sulfate hexahydrate, and the other conditions are exactly the same as those in Example 1.

[0059] Example 3

[0060] The difference from Example 1 is that the metal salt added in step (3) is 0.1781 g of nickel sulfate hexahydrate, and the other conditions are exactly the same as those in Example 1.

[0061] Example 4

[0062] The difference from Example 1 is that the metal salt added in step (3) is 0.1562 g of copper sulfate pentahydrate, and the other conditions are exactly the same as those in Example 1.

[0063] Example 5

[0064] The difference from Example 1 is that the volume of citric acid in step (3) is 40 ml, and the other conditions are exactly the same as those in Example 1.

[0065] Example 6

[0066] The difference from Example 1 is that the volume of citric acid in step (3) is 160 ml, and the other conditions are exactly the same as those in Example 1.

[0067] Example 7

[0068] The difference from Example 1 is that the volume of citric acid in step (3) is 200 ml, and the other conditions are exactly the same as those in Example 1.

[0069] Example 8

[0070] The difference from Example 1 is that the mass of silicon dioxide in step (3) is 60 mg, and the other conditions are exactly the same as those in Example 1.

[0071] Example 9

[0072] The difference from Example 1 is that the mass of silicon dioxide in step (3) is 100 mg, and the other conditions are exactly the same as those in Example 1.

[0073] Example 10

[0074] The difference from Example 1 is that the mass of silicon dioxide in step (3) is 160 mg, and the other conditions are exactly the same as those in Example 1.

[0075] Embodiment 11

[0076] The difference from Example 1 is that the mass of ferrous sulfate heptahydrate added in step (3) is 0.0493 g, and the other conditions are exactly the same as those in Example 1.

[0077] Example 12

[0078] The difference from Example 1 is that the mass of ferrous sulfate heptahydrate added in step (3) is 0.0993 g, and the other conditions are exactly the same as those in Example 1.

[0079] Embodiment 13

[0080] The difference from Example 1 is that the mass of ferrous sulfate heptahydrate added in step (3) is 0.3969 g, and the other conditions are exactly the same as those in Example 1.

[0081] Embodiment 14

[0082] The difference from Example 1 is that the mass of ferrous sulfate heptahydrate added in step (3) is 0.5961 g, and the other conditions are exactly the same as those in Example 1.

[0083] Embodiment 15

[0084] The difference from Example 1 is that the mass of ferrous sulfate heptahydrate added in step (3) is 0.7944 g, and the other conditions are exactly the same as those in Example 1.

[0085] Example 16

[0086] The difference from Example 1 is that the mass of ferrous sulfate heptahydrate added in step (3) is 0.9917 g, and the other conditions are exactly the same as those in Example 1.

[0087] Embodiment 17

[0088] The difference from Example 1 is that the mass of ferrous sulfate heptahydrate added in step (3) is 1.4881 g, and the other conditions are exactly the same as those in Example 1.

[0089] Embodiment 18

[0090] The difference from Example 1 is that the reaction temperature in step (4) is 50° C., and the other conditions are exactly the same as in Example 1.

[0091] Embodiment 19

[0092] The difference from Example 1 is that the reaction temperature in step (4) is 60° C., and the other conditions are exactly the same as in Example 1.

[0093] Embodiment 20

[0094] The difference from Example 1 is that the reaction temperature in step (4) is 80° C., and the other conditions are exactly the same as those in Example 1.

[0095] Embodiment 21

[0096] The difference from Example 1 is that the reaction temperature in step (4) is 90° C., and the other conditions are exactly the same as those in Example 1.

[0097] Embodiment 22

[0098] The difference from Example 1 is that the reaction time in step (4) is 2 h, and the other conditions are exactly the same as in Example 1.

[0099] Embodiment 23

[0100] The difference from Example 1 is that the reaction time in step (4) is 6 h, and the other conditions are exactly the same as in Example 1.

[0101] Embodiment 24

[0102] The difference from Example 1 is that the reaction time in step (4) is 8 h, and the other conditions are exactly the same as in Example 1.

[0103] Embodiment 25

[0104] The difference from Example 1 is that the reaction time in step (4) is 12 h, and the other conditions are exactly the same as in Example 1.

[0105] Embodiment 26

[0106] The difference from Example 1 is that the reaction time in step (4) is 24 h, and the other conditions are exactly the same as those in Example 1.

[0107] Embodiment 27

[0108] The difference from Example 25 is that the mass of ferrous sulfate heptahydrate added in step (3) is 0.7944 g, and the other conditions are exactly the same as in Example 25.

[0109] Comparative Example 1

[0110] The difference from Example 1 is that no metal salt is added, and other conditions are exactly the same as those in Example 1.

[0111] Comparative Example 2

[0112] The difference from Example 1 is that silicon dioxide is not added, and other conditions are exactly the same as those in Example 1.

[0113] The leaching rates of cobalt and lithium in waste lithium cobalt oxide batteries by the treatment methods of Examples 1-27 and Comparative Examples 1-2 are compared:

[0114] 1) The X-ray diffraction patterns of the raw materials, the leached residues of Example 1 and Comparative Example 1 are as follows: Figure 1 As shown by Figure 1It can be seen that all samples show a main diffraction peak at about 18.5° of 2θ, which is consistent with the standard card of lithium cobalt oxide (LiCoO2, PDF#75-0532), confirming the presence of lithium cobalt oxide in the precipitate. Compared with the raw material, the diffraction peaks of Example 1 and Comparative Example 1 are slightly shifted to the left by about 0.2°. In addition, Example 1 and Comparative Example 1 show obvious new diffraction peaks at about 26.6° of 2θ value. It is speculated through qualitative analysis that this may be the result of incomplete reaction of the catalyst silicon dioxide. In contrast, the XRD diffraction peak intensity of the raw material is stronger and the peak shape is sharper, indicating that the crystallinity of lithium cobalt oxide is higher and the impurity content is lower.

[0115] 2) By Figure 2 It can be seen that the morphology of Example 1 contains larger particles and a wider particle size distribution. Compared with Example 27, the leached residue after leaching has a layered structure, a narrower particle size distribution, and a smaller particle size. Figure 2 and Figure 3 Comparative analysis shows that the addition of ferrous ions exhibits excellent reduction and leaching properties, and can effectively leach waste cathode materials. Figure 2 The microscopic images shown show that the sample contains larger particles with a wider distribution of particle sizes. Figure 3 The leached residues shown have a layered structure with a narrow particle size distribution and a small overall particle size. This change indicates that significant physical structural changes occurred during the leaching process. Figure 2 and Figure 3 The addition of ferrous ions enhanced the leaching effect. The layered structure and smaller particle size usually have a higher specific surface area, indicating that the area available for reaction on the surface of the filter residue is relatively large, which may make the contact electrocatalysis more efficient.

[0116] 3) The effects of different metal sulfates on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries were investigated. The concentrations of cobalt and lithium in the battery leachates treated by the methods of Examples 1-4 and Comparative Example 1 were compared with the efficiency of the completely digested leachate. The comparison results are as follows: Figure 4 shown.

[0117] Figure 4 The results show that by adding different types of metal salts, such as ferrous sulfate, cobalt nitrate, nickel sulfate and copper sulfate, it can be found that cobalt nitrate, nickel sulfate and copper sulfate have an inhibitory effect on the leaching of waste lithium cobalt oxide batteries. Ferrous sulfate increases the leaching efficiency of cobalt and lithium by 6.5% and 6.6% respectively, which is of practical significance for further exploring whether the addition of ferrous ions can promote the leaching of metal ions in waste lithium batteries.

[0118] 4) The effect of different volumes of citric acid on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries was investigated. The concentrations of cobalt and lithium in the battery leachates treated by the methods of Examples 1 and 5-7 were compared with the efficiency of the completely digested leachates. The comparison results are shown in FIG. Figure 5 shown.

[0119] Figure 5 It shows that by adding different volumes of citric acid to change the solid-liquid ratio of the reaction, it can be found that with the increase of citric acid volume, the leaching rate of waste lithium cobalt oxide batteries is gradually increasing. The amount of citric acid added plays a promoting role in the leaching rate. When 200 ml of citric acid is added, the leaching rates of cobalt and lithium can reach 60.8% and 77.7%.

[0120] 5) The effect of different qualities of silicon dioxide on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries was investigated. The concentrations of cobalt and lithium in the battery leachates treated by the methods of Example 1, Examples 8-10 and Comparative Example 2 were compared with the efficiency of the completely digested leachate. The comparison results are as follows: Figure 6 shown.

[0121] Figure 6 It shows that by analyzing the leaching rate of adding different masses of silicon dioxide, it can be found that adding 60 mg of silicon dioxide can increase the leaching rate of cobalt and lithium by 4.6% and 0.2% respectively. Subsequently, when the silicon dioxide content continues to increase, the leaching rate remains at this level, indicating that only a small amount of silicon dioxide is needed to increase the leaching rate of cobalt in waste lithium cobalt oxide batteries.

[0122] 6) The influence of different masses of ferrous ions on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries was investigated. The concentrations of cobalt and lithium in the battery leachates treated by the methods of Examples 1 and 11-17 were compared with the efficiency of the completely digested leachates. The comparison results are shown in FIG. Figure 7 shown.

[0123] Figure 7 It shows that by comparing the leaching rates of adding different masses of ferrous ions, it can be found that with the increase of ferrous ion content, the leaching rate shows a trend of first inhibition and then promotion. When the ferrous ion content is 160 mg, the leaching rate reaches a peak value, and the leaching rates of cobalt and lithium are 90.8% and 94.7% respectively. Subsequently, ferrous ions continue to be added on this basis, and the leaching rate changes little.

[0124] 7) The effect of different reaction temperatures on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries was investigated. The concentrations of cobalt and lithium in the battery leachates treated by the methods of Examples 1 and 18-21 were compared with the efficiency of the completely digested leachates. The comparison results are as follows: Figure 8 shown.

[0125] Figure 8It shows that by comparing the leaching rates at different reaction temperatures, it can be found that the reaction temperature plays a promoting role on waste lithium cobalt oxide batteries. As the reaction temperature increases, the leaching rate also increases synchronously. When the reaction temperature is 90°C, the leaching rates of cobalt and lithium reach 67.3% and 79.8% respectively.

[0126] 8) The effect of different reaction times on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries was investigated. The concentrations of cobalt and lithium in the battery leachates treated by the methods of Examples 1 and 22-26 were compared with the efficiency of the completely digested leachates. The comparison results are as follows: Fig. 9 shown.

[0127] Fig. 9 It shows that by comparing the leaching rates at different reaction times, it can be found that the reaction time plays a promoting role on waste lithium cobalt oxide batteries. The leaching rate changes very little when the reaction time is 4h, 6h and 8h, but as the reaction time increases, when the reaction time is 24h, the leaching rates of cobalt and lithium can reach more than 90%, which are 91.1% and 90.1% respectively.

[0128] 9) The effect of the optimal conditions on the leaching rate of cobalt and lithium in waste lithium cobalt oxide batteries was investigated. The concentrations of cobalt and lithium in the battery leachates treated by the methods of Example 1 and Example 27 were compared with the efficiency of the completely digested leachate. The comparison results are as follows: Fig.10 shown.

[0129] Fig.10 It is shown that by comparing the leaching rates of Example 1 and Example 27, it can be found that the leaching rates of cobalt and lithium in Example 27 are 94.14% and 100%, respectively.

[0130] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.

Claims

1. A method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries, characterized in that: Including the following processes: S1. Obtain the positive electrode sheet of the waste lithium battery and crush it to obtain the positive electrode active powder; S2. Place the three-necked flask in a water bath ultrasonic pot, with the left port for placing the condenser, the central port for placing the stirrer, and the right port for adding the reagent; S3. The organic acid was added to the three-necked flask through the right port, and silica, metal salt, and positive electrode active powder were added successively to obtain a mixed solution; S4. The reagents in step S3 are mixed evenly using a water bath ultrasonic pot and a stirrer, and the reaction is completed to obtain a liquid after the reaction; S5. The liquid after the reaction in step S4 is subjected to solid-liquid separation and washed several times to obtain separated solids and liquids; S6. Add a set amount of nitric acid to the liquid described in step S5 to prevent metal hydrolysis and precipitation, and then use deionized water to make the volume to 1L to obtain a leaching solution containing metallic cobalt and lithium.

2. A method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The waste lithium batteries include a mixture of one or more of lithium cobalt oxide batteries, lithium manganese oxide batteries, lithium iron phosphate batteries, etc.

3. The method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The organic acid includes a mixture of one or more of citric acid, malic acid, etc.

4. The method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The organic acid concentration is 0.15-0.25 mol / L, and the organic acid volume is 40-200 ml.

5. The method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The mass of the silicon dioxide is 0-160 mg.

6. The method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The metal salt includes a mixture of one or more of ferrous sulfate, manganese sulfate, cobalt nitrate, nickel sulfate, copper sulfate and the like.

7. The method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The reaction conditions in step S4 are as follows: the temperature of the water bath ultrasonic pot is 50-90° C., the reaction time is 2-24 h, and the speed of the stirrer is 400-600 rpm.

8. The method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The set amount of nitric acid is 0.5-2 ml.

9. The method for enhancing the leaching of valuable metals from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: The mass of the metal ions in the metal salt is 40-300 mg.

Citation Information

Cited By

  • Method for recycling positive electrode material of lithium ion battery

    CN120413861A